2001
DOI: 10.1128/aem.67.9.3908-3922.2001
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Spatial Variability in Lake Michigan Sediment Small-Subunit rRNA Concentrations

Abstract: We have used molecular biological methods to study the distribution of microbial small-subunit rRNAs (SSU rRNAs), in relation to chemical profiles, in offshore Lake Michigan sediments. The sampling site is at a depth of 100 m, with temperatures of 2 to 4°C year-round. RNA extracted from sediment was probed with radiolabeled oligonucleotides targeting bacterial, archaeal, and eukaryotic SSU rRNAs, as well as with a universal probe. The coverage of these probes in relation to the present sequence database is dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…A solution to this problem might be to target RNA molecules directly instead of their genes. As opposed to rRNA genes, significant quantities of rRNA are produced only in active microbes (46). The heterotrophic stramenopiles detected in our study were restricted to the chemocline (18 m) and lower redox transition zone (23 m) (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…A solution to this problem might be to target RNA molecules directly instead of their genes. As opposed to rRNA genes, significant quantities of rRNA are produced only in active microbes (46). The heterotrophic stramenopiles detected in our study were restricted to the chemocline (18 m) and lower redox transition zone (23 m) (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Euryarchaeota had previously been detected by phylogenetic analyses in sediments of temperate freshwater environments (e.g. MacGregor et al 1997, Abreu et al 2001 but not in the water column (Crump & Baross 2000). Recently, using universal archaeal primers developed for soil Archaea, Galand et al (2006) identified 2 novel euryarchaeotal groups, Rice Cluster-V (RC-V) and Lake Dagow Sediment (LDS), in the water of a large Arctic river, the Mackenzie River, during maximum open water conditions (October 2002).…”
Section: Diversity Of Archaeamentioning
confidence: 91%
“…16S rRNA sequences belonging to non-extremophilic aquatic Archaea were first discovered in the oxygenated water column of the Pacific and Atlantic Oceans (DeLong 1992, Fuhrman et al 1992; however, it is now clear that these organisms are ubiquitously present in marine systems (Massana et al 2000, Herndl et al 2005, Wuchter 2006, Wuchter et al 2006b), lakes (MacGregor et al 1997, Schleper et al 1997, Keough et al 2003) and rivers (Crump & Baross 2000, Abreu et al 2001, Bouvier & del Giorgio 2002, Galand et al 2006, 2008, Garneau et al 2006. Several studies have focused on the distribution of archaeal assemblages in the water column and sediments along salinity gradients in estuaries (Crump & Baross 2000, Abreu et al 2001, Bouvier & del Giorgio 2002.…”
Section: Introductionmentioning
confidence: 99%
“…The stratified water column in the Black Sea is believed to host more active and diverse microbial assemblages than anywhere else in the pelagic ocean (14). As such, the Black Sea is an excellent model system for studying oxic/anoxic interfaces, essentially stretching a chemocline normally encountered on the submillimeter scale over tens of meters.Although other oxic/anoxic regions exist and reports of molecular characterization of microbial communities from the Cariaco Trench (23) or sedimentary systems (12,22,40,42) have been published, few systematic profiles of the transition between oxic and anoxic bacterial communities beyond a domain-or group-specific approach have been reported. The purpose of this study was to characterize the Bacteria and Archaea populations in the Black Sea at a species-specific level and to correlate the vertical distribution of the various prokaryotic plankton with the profiles of terminal electron acceptors that occur throughout the oxic/anoxic chemocline.…”
mentioning
confidence: 99%